Impact of published clinical outcomes data: case study in NHS hospital trusts. Issue 7307 (4th August 2001) - Mannion, Russell; Goddard, Maria
Abstract: Objective: To examine the impact of the publication of clinical outcomes data on NHS Trusts in Scotland to inform the development of similar schemes elsewhere. Design: Case studies including semistructured interviews and a review of background statistics. Setting: Eight Scottish NHS acute trusts. Participants: 48 trust staff comprising chief executives, medical directors, stroke consultants, breast cancer consultants, nurse managers, and junior doctors. Main outcome measures: Staff views on the benefits and drawbacks of clinical outcome indicators provided by the clinical resource and audit group (CRAG) and perceptions of the impact of these data on clinical practice and continuous improvement of quality. Results: The CRAG indicators had a low profile in the trusts and were rarely cited as informing internal quality improvement or used externally to identify best practice. The indicators were mainly used to support applications for further funding and service development. The poor effect was attributable to a lack of professional belief in the indicators, arising from perceived problems around quality of data and time lag between collection and presentation of data; limited dissemination; weak incentives to take action; a predilection for process rather than outcome indicators; and a belief that informal information is often more useful than quantitative data in the assessment of clinical performance. Conclusions: Those responsible for developing clinical indicator programmes should develop robust datasets. They should also encourage a working environment and incentives such that these data are used to improve continuously.